2020
DOI: 10.1371/journal.pone.0233462
|View full text |Cite
|
Sign up to set email alerts
|

The theory of planned behavior as a behavior change model for tobacco control strategies among adolescents in Botswana

Abstract: Background Behavioral intentions (motivational factors), attitudes, subjective norm (social pressures), and perceived behavioral control promote or discourage smoking behavior among adolescents. Objective To assess students' behavioral intentions, attitudes, subjective norms and perceived behavioral control on smoking using the Theory of Planned Behavior. The prevalence of smoking among the adolescents is also calculated. Methods In this cross-sectional study, structured self-administered questionnaires were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 52 publications
2
27
0
2
Order By: Relevance
“…For this, it is necessary to help parents and adults improve adolescents' ability to implement COVID-19 preventive behavior. Additionally, because adolescents tend to imitate their parents' behaviors ( Tapera et al, 2020 ), parents should become role models to their children and promote COVID-19 preventive behaviors. However, many parents find it burdensome to educate their children about these behaviors because of the suspension of schools, having to work from home, and enduring economic difficulties, as well as managing their own fear and anxiety about the pandemic ( Witt et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For this, it is necessary to help parents and adults improve adolescents' ability to implement COVID-19 preventive behavior. Additionally, because adolescents tend to imitate their parents' behaviors ( Tapera et al, 2020 ), parents should become role models to their children and promote COVID-19 preventive behaviors. However, many parents find it burdensome to educate their children about these behaviors because of the suspension of schools, having to work from home, and enduring economic difficulties, as well as managing their own fear and anxiety about the pandemic ( Witt et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…42 Factors that contribute to tobacco smoking among students include attitudes and subjective norms. 46 A study of HIVinfected smokers reported the feasibility of a behavioural intervention for tobacco cessation. 47 Depression.…”
Section: Areas Of Mental Health Addressed In the Studiesmentioning
confidence: 99%
“…Adolescents are more prone to smoking if they were in a peer group that smokes [3]. The influence of the family on adolescent smoking is mainly due to the direct effects of family poverty, smoking parents, and family processes [4], [5].…”
Section: Introductionmentioning
confidence: 99%